2020
DOI: 10.3390/cancers12092357
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-11 Promotes Early Mouse Mammary Gland Tumor Growth through Metabolic Reprogramming and Increased IGF1/AKT/FoxO1 Signaling Pathway, Enhanced ER Stress and Alteration in Mitochondrial UPR

Abstract: Matrix metalloproteinase 11 (MMP11) is an extracellular proteolytic enzyme belonging to the matrix metalloproteinase (MMP11) family. These proteases are involved in extracellular matrix (ECM) remodeling and activation of latent factors. MMP11 is a negative regulator of adipose tissue development and controls energy metabolism in vivo. In cancer, MMP11 expression is associated with poorer survival, and preclinical studies in mice showed that MMP11 accelerates tumor growth. How the metabolic role of MMP11 contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Therefore, human metabolic pathway subgroups were retrieved from the NCBI GEO database and used for induction. A heat map on the correlation between core genes and metabolic pathways showed that main changes are changes in the metalloproteinase families [40,41] and their tissue-specific inhibitory enzyme familyrelated factors. Moreover, Gene Ontology functional enrichment analysis showed that decomposition of collagen and ECM is the main source of disc degeneration differences [19,42,43].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…Therefore, human metabolic pathway subgroups were retrieved from the NCBI GEO database and used for induction. A heat map on the correlation between core genes and metabolic pathways showed that main changes are changes in the metalloproteinase families [40,41] and their tissue-specific inhibitory enzyme familyrelated factors. Moreover, Gene Ontology functional enrichment analysis showed that decomposition of collagen and ECM is the main source of disc degeneration differences [19,42,43].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…Mice were subjected to the intraperitoneal injection of [U- 13 C]-glucose for 48 h before being sacrificed. This work was done as part of a study on the impact of MMP11 on tumor progression in the PyMT-MMTV mouse model of mammary tumors . The final insert used for the experiment contained 14 mg of biopsy specimen and 5 μL of D 2 O.…”
Section: Methodsmentioning
confidence: 99%
“…This work was done as part of a study on the impact of MMP11 on tumor progression in the PyMT-MMTV mouse model of mammary tumors. 15 The final insert used for the experiment contained 14 mg of biopsy specimen and 5 μL of D 2 O.…”
mentioning
confidence: 99%
“…An alteration to the MMP expression or in the balance between MMPs and their tissue-specific inhibitors is crucial for ECM remodeling during normal tissue development and disease progression. During obese development, an increased expression of MMP3, MMP11, MMP12, MMP13, and MMP14 has been detected and a reduction in MMP7, MMP9, MMP16, and MMP24 has been detected [ 55 , 56 , 57 ]. MMP13 cleaves interstitial collagens such as type I and III.…”
Section: Obesity-associated Fibrosis and Ecm Remodelingmentioning
confidence: 99%
“…MMP13 cleaves interstitial collagens such as type I and III. MMP3 and MMP7 are mainly involved in fibronectin degradation [ 55 , 56 , 57 ]. Among these MMPs, MMP14 (MT1-MMP1) is the predominant pericellular collagenase in adipose tissue [ 55 ].…”
Section: Obesity-associated Fibrosis and Ecm Remodelingmentioning
confidence: 99%